2019
DOI: 10.1101/753608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homeostatic plasticity rules that compensate for cell size are susceptible to channel deletion

Abstract: Neurons can increase in size dramatically during growth. In many species neurons 8 must preserve their intrinsic dynamics and physiological function across several length scales. For 9 example, neurons in crustacean central pattern generators generate similar activity patterns 10 despite multiple-fold increases in their size and changes in morphology. This scale invariance hints 11 at regulation mechanisms that compensate for size changes by somehow altering membrane 12 currents. Using conductance-based neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…29 Because the scientific literature dealing with ion channels provides detailed insights regarding the activitydependent compensation of cell size linked with ion channels, this work focused on the analysis of anion channels as possible mediators of the cellular effects of azaspiracids. 57 It has been previously demonstrated that AZA1 alters the cellular cytoskeleton. 23,[25][26][27]29 In this work, we found that exposure of human cells to AZA1 increased chloride mediated currents in nonexcitable cells, a fact that could be linked to the cell cytoskeleton, because azaspiracids could affect membrane unfolding protein interactions such as alpha-actinin 4 (ACTN4) and thus upregulate anion channel activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…29 Because the scientific literature dealing with ion channels provides detailed insights regarding the activitydependent compensation of cell size linked with ion channels, this work focused on the analysis of anion channels as possible mediators of the cellular effects of azaspiracids. 57 It has been previously demonstrated that AZA1 alters the cellular cytoskeleton. 23,[25][26][27]29 In this work, we found that exposure of human cells to AZA1 increased chloride mediated currents in nonexcitable cells, a fact that could be linked to the cell cytoskeleton, because azaspiracids could affect membrane unfolding protein interactions such as alpha-actinin 4 (ACTN4) and thus upregulate anion channel activity.…”
Section: ■ Discussionmentioning
confidence: 99%
“…It has recently been shown theoretically by Cuntz et al (2019) [ 23 ] that these two phenomena cancel each other exactly: the excitability of neurons receiving distributed excitatory synaptic inputs is largely invariant to changes in size and morphology. In addition, neurons possess several compensatory mechanisms to help maintain firing-rate homeostasis through both synaptic plasticity regulating inputs [ 24 , 25 ] and changes in membrane conductance regulating responses [ 26 , 27 ]. These results imply a consistent biophysical mechanism that contributes to stability in neuronal activity despite changes in scale and connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown by Cuntz et al (2019) that these two phenomena 21 cancel each other exactly: the excitability of neurons receiving distributed excitatory synaptic inputs is largely 22 invariant to changes in size and morphology. In addition, neurons possess several active mechanisms to help 23 maintain firing-rate homeostasis through both synaptic plasticity regulating inputs (Abbott & Nelson, 2000;24 Royer & Paré, 2003) and changes in membrane conductance regulating responses (Gorur-Shandilya et al, 2019). 25 These results imply a consistent biophysical mechanism that contributes to stability in neuronal activity despite 26 changes in scale and connectivity.…”
mentioning
confidence: 99%